Application of the Teaching at the Right Level Approach to Improve Learning Outcomes of Class X NKPI APHP Students at SMK Negeri 7 Palu on Opportunity Material - Ma’rifah, Amilatul; Hermiyati, Yosepha Endang; Hasbi, Muh (CV. Rayyan Dwi Bharata, 2025)
Low learning outcomes are one of the biggest challenges faced by mathematics teachers at SMK Negeri 7 Palu. Therefore, a teacher needs to design an interesting and innovative learning activity so that it can improve students' learning outcomes. This study aims to improve students' learning outcomes through the application of the Teaching at the Right (TaRL) approach. This study uses a type of collaborative classroom action research involving 16 class X NKPI APHP students consisting of 11 male students and 5 female students. Based on the results of the classroom action research carried out for 2 cycles, information was obtained that mathematics learning outcomes through the application of the Teaching at the Right (TaRL) approach always increased. This is evidenced by the increase in the average learning outcomes of students from the pre-cycle of 58 (before applying the Teaching at the Right approach) to 79 in cycle 1 and increased again to 87 in cycle 2. This shows that the application of the Teaching at the Right (TaRL) approach in class X NKPI APHP SMK Negeri 7 Palu has succeeded in improving learning outcomes in mathematics subjects.